The Distinctiveness of Christian Gratitude: A Theological Survey - Kent Dunnington (Religions, 2022)
The positive psychology movement has increased and deepened our understanding of gratitude and its contribution to human well-being. Most of the literature to date has focused on gratitude to human benefactors, and the same has been true of philosophical analyses of gratitude. More recently, scholars of gratitude have turned their attention to gratitude to God, but relatively little work has been done on the relationship between particular theologies and spiritualities on the one hand and the phenomenology and structure of gratitude on the other. This essay makes a contribution to that strand of investigation by surveying the work of six Christian theologians, each of whom make bold, sometimes cryptic, claims about the distinctiveness of Christian gratitude and gratitude to God. The essay challenges universalist assumptions about the structure and phenomenology of gratitude, including gratitude to God.